PENERAPAN SMART WASTE MANAJEMEN PADA BANK SAMPAH SS SIDO RESIK CEMBING TRIMULYO JETIS BANTUL - David Sulistiyantoro, David Sulistiyantoro; Gerlan Haha Nusa; Gilang Argya Dyaksa; Aris Wahyu Murdiyanto; Ikbal Rizki Putra (Jurnal Berdaya Mandiri, 2025)
The background of this program lies in the escalating waste management issues in Bantul Regency, which have become increasingly urgent following the closure of the Piyungan Final Waste Processing Site (TPST). The designated partner, SS Sido Resik Waste Bank, encounters three principal challenges: (1) the absence of inorganic waste processing technologies to enhance economic value, (2) the unavailability of equipment to dry wet waste, which complicates the sorting process, and (3) the lack of a system to convert organic waste into compost fertilizer. To address these issues, the implementing team introduced three units of Appropriate Technology (AT): the Plastic Waste Shredding Machine, the Rotary Dryer, and the Organic Magobox. The implementation process was carried out through five systematic stages: socialization, training, technological application, mentoring and evaluation, and sustainability planning. All units of AT were successfully adopted and operated by the partner institution, thereby directly mitigating the identified problems. The adoption of these technologies demonstrated a measurable and positive impact on community empowerment. The Plastic Waste Shredding Machine achieved a 100% utility rate, as it introduced a shredding process that was previously unavailable. The Rotary Dryer attained a 75% utility rate, as reflected in the reduction of drying time from 60 minutes to 15 minutes. The Organic Magobox achieved a 33.3% utility rate, corresponding to its use over 20 days out of the 60-day cycle required for compost production. Keywords: SS Sido Resik, Trimulyo Village Waste Bank, Appropriate Technology, Plastic Shredding Machine, Rotary Dryer, Organic Magobox